Proteomic Analysis of the Schistosoma mansoni Miracidium. - Tianfang Wang; Min Zhao; Bronwyn A Rotgans; April Strong; Di Liang; Guoying Ni; Yanin Limpanont; Pongrama Ramasoota; Donald P McManus; Scott F Cummins (PLoS ONE, 2016)
Despite extensive control efforts, schistosomiasis continues to be a major public health problem in developing nations in the tropics and sub-tropics. The miracidium, along with the cercaria, both of which are water-borne and free-living, are the only two stages in the life-cycle of Schistosoma mansoni which are involved in host invasion. Miracidia penetrate intermediate host snails and develop into sporocysts, which lead to cercariae that can infect humans. Infection of the snail host by the miracidium represents an ideal point at which to interrupt the parasite's life-cycle. This research focuses on an analysis of the miracidium proteome, including those proteins that are secreted. We have identified a repertoire of proteins in the S. mansoni miracidium at 2 hours post-hatch, including proteases, venom allergen-like proteins, receptors and HSP70, which might play roles in snail-parasite interplay. Proteins involved in energy production and conservation were prevalent, as were proteins predicted to be associated with defence. This study also provides a strong foundation for further understanding the roles that neurohormones play in host-seeking by schistosomes, with the potential for development of novel anthelmintics that interfere with its various life-cycle stages.